Senyum Pesisir : Program Peningkatan Derajat Kesehatan Gigi dan Mulut Masyarakat Kawasan Perikanan - Faradillah Usman; Zulkarnain Zulkarnain; Dwi Rezky Aulyah; Febi Magfirah; Wirda Aulia; Fidzah Nur Fajrina Murad; Destriana Aris (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Oral health is an integral part of general health and plays an essential role in improving people's quality of life. Coastal fishing communities are at higher risk of experiencing oral health problems due to limited knowledge, inadequate oral hygiene practices, and restricted access to dental health services. This community service program aimed to improve the knowledge, awareness, and skills of coastal communities in maintaining oral health through the Senyum Pesisir (Coastal Smile) program conducted in Bonto Mate'ne Village, Marusu District, Maros Regency. The program employed oral health education, tooth-brushing demonstrations using dental phantom models, oral health examinations, supervised tooth-brushing practice, and evaluation through pre-test and post-test questionnaires. The activities were implemented through preparation, implementation, evaluation, and follow-up stages involving lecturers, students, village officials, community health center personnel, and local residents. The results indicated an improvement in participants' knowledge and understanding regarding the importance of oral health, proper tooth-brushing techniques and timing, and the importance of regular dental check-ups. Participants also demonstrated a high level of enthusiasm and were able to correctly perform tooth-brushing techniques after the educational intervention. This program is expected to serve as a sustainable promotive and preventive strategy to improve the oral health status of coastal communities through collaboration among higher education institutions, local government, health professionals, and the community.